Нові місцезнаходження рідкісних видів Sternbergia colchiciflora Waldst. et Kit. (Amaryllidaceae) та Bulbocodium versicolor (Ker Gawl.) Spreng. (Colchicaceae) в Південній Беcсарабії - Мельник, В.І.; Діденко, С.Я. (Український ботанічний журнал, 2013)
Описаны новые местонахождения редких видов Sternbergia
colchiciflora и Bulbocodium versicolor в Южной Бессарабии. Освещено современное состояние популяций этих видов. Предложены рекомендации по улучшению охраны растений в
Одесской обл. New localities of rare species, Sternbergia colchiciflora and Bul boco
dium versicolor, in Southern Bessarabia are described. The current
state of their populations is considered. Recommendations
for the improvement of plant conservation in Odessa Region are
proposed.